The Charter and Ordinances of the City of St. Paul 166-67 (1863) - (:unkn) unknown (My University, 1858)
Ch. 21, §§ 1-5: Prohibited the keeping, sale, or giving away of gun powder or gun cotton "in any quantity" absent payment of $5 to the City Treasurer and written permission of the authorities. Authorized any person to "keep for his own use" no more than 1 pound of gun powder or gun cotton at any one time. Punishable by a fine not to exceed $50 per offense.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER